Knowledge, Attitude and Practice on Electronic Cigarette and their Associated Factors among Undergraduate Students in a Public University - Nuurain Amirah MR,; Tengku Amatullah Madeehah TM ,; Nadeeya ‘Ayn MN,; Dzulkhairi MR,; Mohamed Fakhri AB,; Shalinawati R,; Nooriah MS,; Jaafar H.; Zairina A. Rahman (IIUM Press, 2024)
Indexed by WOS/SCOPUS/MYCITE